Molecular analysis of brazilian patients with combined pituitary hormone deficiency and orthotopic posterior pituitary lobe reveals eight different PROP1 alterations with three novel mutations. (4th September 2017) - Madeira, Joao LO; Nishi, Mirian Y; Nakaguma, Marilena; Benedetti, Anna F; Biscotto, Isabela Peixoto; Fernandes, Thamiris; Pequeno, Thiago; Figueiredo, Thalita; Franca, Marcela M; Correa, Fernanda A; Otto, Aline P; Abrão, Milena; et al.
Summary: Background: Mutations in PROP1, HESX1 and LHX3 are associated with combined pituitary hormone deficiency (CPHD) and orthotopic posterior pituitary lobe (OPP). Objective: To identify mutations in PROP1, HESX1 and LHX3 in a large cohort of patients with CPHD and OPP (35 Brazilian, two Argentinian). Design and Methods: We studied 23 index patients with CPHD and OPP (six familial and 17 sporadic) as well as 14 relatives. PROP1 was sequenced by the Sanger method in all except one sporadic case studied using a candidate gene panel. Multiplex ligation‐dependent probe amplification (MLPA) was applied to one familial case in whom PROP1 failed to amplify by PCR. In the 13 patients without PROP1 mutations, HESX1 and LHX3 were sequenced by the Sanger method. Results: We identified PROP1 mutations in 10 index cases. Three mutations were novel: one affecting the initiation codon (c.1A>G) and two affecting splicing sites, c.109+1G>A and c.342+1G>C. The known mutations, c.150delA (p.Arg53Aspfs*112), c.218G>A (p.Arg73His), c.263T>C (p.Phe88Ser) and c.301_302delAG (p.Leu102Cysfs*8), were also detected. MLPA confirmed complete PROP1 deletion in one family. We did not identify HESX1 and LHX3 mutations by Sanger. Conclusion: PROP1 mutations are a prevalent cause of congenital CPHD with OPP, and therefore, PROP1 sequencing must be the first step of molecular investigation in patients with CPHD and OPP, especially in populations with a high frequency of PROP1 mutations. In the absence of mutations, massively parallel sequencing is a promising approach. The high prevalence and diversity of PROP1 mutations is associated with the ethnic background of this cohort.